THERMODYNAMIC AND HEAT TRANSFER ANALYSIS OF COOLING TECHNOLOGIES: A COMPARATIVE STUDY - Novais, W. R. I.; Cerqueira, E. P.; Narváez-Romo, B.; Simões-Moreira, J. R. (Revista de Engenharia Térmica, 2022)
Refrigeration systems applications are broadly used in food and drug conservation and in air conditioning systems. Commercial buildings may demand as much as 80% of total electrical power just for powering the air-conditioning system based on conventional vapor compression refrigeration systems (VCRS), which contributes to reach peak demands on the electrical distribution network that could cause an unstable condition. Implementing absorption refrigeration systems (ARS) to produce cooling effects driven by thermal energy could decrease that power demand. Thermodynamic models of these systems can be found in the literature with a variety of working fluids and also integrated with other cycles such as power generation plants. However, a few previous analyses have a direct comparison between ARS and VCRS at the same operational conditions. Thus, the current study aims to simulate and compare two different refrigeration technologies: single stage ammonia-water absorption refrigeration system and vapor compression refrigeration system working with refrigerants R-134a and R-717. Thermodynamic simulation was carried out by evaluating heat transfer rates in the main devices, coefficients of performance, and specific areas of evaporator and condenser. As evaporator temperature decreases from 10°C to -20°C, ARS requires 16.9 kW or 67.5% more heat in generator and COP decreased from 0.601 to 0.359. Utilizing the same comparison parameter, VCRS needed 3.26-3.54 kW or 154-160% more compressor power, depending on refrigerant used, and COP decreased from 6.77 to 2.60 with R-134a and 7.07 to 2.79 using R-717 at the same condensation temperature (40°C). Compared to ARS, condenser specific area required for VCRS is smaller, evaporator is twofold smaller when using R-134a, and is equal when using R-717. Those results can justify the usage of ARS in facilities with high amount of waste heat, mainly on applications working with lower evaporator temperatures.